Covert data transmission using secret-sharing and network steganography - Islam, Mohammad Ariful; Simran, Shahrin Shafiq; Aseef, Mahir; Rahman, Labiba (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.